Grating Lobes Reduction in an Array Antenna Using Curved Disc Monopoles (ELEKTRIKA- Journal of Electrical Engineering, 2022)
This paper shows the study of an array antenna with curved disc monopoles whose average spacing between elements is greater than a wavelength l0. The proposed antenna is a linear array, consisting of four equally spaced curved disc monopoles excited by a corporate feed (T-junction power divider). The single element is characterized by a directional radiation pattern in the H plane. Compared to an isotropic monopole antenna array, the proposed array reduces the grating lobes to more than -15dB. As a result, the gain will be increased. The array antenna is fabricated and measured for its impedance and radiation characteristics. The results of the simulation and measurement are in good agreement.